Topographic metrics for unveiling fault segmentation and tectono-geomorphic evolution with insights into the impact of inherited topography, Ulsan Fault Zone, South Korea - Lee, Cho-Hee; Seong, Yeong Bae; Weber, John; Ha, Sangmin; Kim, Dong-Eun; Yu, Byung Yong (Copernicus Publications, 2024)
Quantifying today's topography can provide insights into landscape evolution and its controls, since present topography represents a cumulative expression of past and present surface processes. The Ulsan Fault Zone (UFZ) is an active fault zone on the southeastern Korean Peninsula that was reactivated as a reverse fault around 5 Ma. The UFZ strikes NNW-SSE and dips eastward. This study investigates the relative tectonic activity along the UFZ and the landscape evolution of the hanging-wall side of the UFZ, focusing on neotectonic perturbations using 10Be-derived catchment-averaged denudation rates and bedrock incision rates, topographic metrics, and a landscape evolution model. Five geological segments were identified along the fault, based on their relative tectonic activity and fault geometry. We simulated four cases of landscape evolution to investigate the geomorphic processes and accompanying topographic changes in the study area in response to fault movement. Model results reveal that the geomorphic processes and the patterns of topographic metrics (e.g., chi anomalies) depend on inherited topography (i.e., the topography that existed prior to reverse fault reactivation of the UFZ). On the basis of this important model finding and additional topographic metrics, we interpret the tectono-geomorphic history of the study area as follows: (1) the northern part of the UFZ has been in a transient state and is in topographic and geometric disequilibrium, so this segment underwent asymmetric uplift (westward tilting) prior to reverse faulting on the UFZ around 5 Ma, and (2) its southern part was negligibly influenced by the asymmetric uplift before reverse faulting. Our study demonstrates the utility of topographic metrics as reliable criteria for resolving fault segments. Together with landscape evolution modeling, topographic metrics provide powerful tools for examining the influence of inherited topography on present topography and for the elucidation of tectono-geomorphic histories.